Kinetic Parameters of E. coli Growth After Deep Freezing at Diethyl Sulfoxide Presence - Markarian, S. A.; Bagramyan, K. A.; Arakelyan, V. B. (Problems of Cryobiology and Cryomedicine, 2006)
Specific growth rate and lag-phase of E.coli before and after their deep freezing under â€“196Â°C temperature at the presence of diethyl sulfoxide (DESO) in 10% concentration were investigated. The results were compared with the data obtained during investigations of traditional cryoprotectants of glycerol and dimethyl sulfoxide (DMSO). It is shown, that under physiological conditions the cryoprotectants reduce a specific growth rate, moreover the strongest effect is caused by DESO. After freezing the specific growth rate is increased and its value is practically equal under control conditions and at the presence of glycerol, DMSO and DESO. It is demonstrated, that the DESO presence in a cultural liquid practically declines the lag-phase both before and after E.coli freezing.